Assembly of phagocyte NADPH oxidase: A concerted binding process? - Karimi, Gilda; Houée Levin, Chantal; Dagher, Marie Claire; Baciou, Laura; Bizouarn, Tania (Biochimica et biophysica acta, 2014)
The phagocyte NADPH-oxidase is a multicomponent enzyme that generates superoxide anions. It comprises a membrane redox component flavocytochrome b558 and four cytosolic proteins (p67phox, p47phox, p40phox and Rac) that must assemble to produce an active system. In this work we focused on the spatio-temporal control of the activation process of phagocyte NADPH oxidase. A wide range of techniques including fast kinetics with a stopped-flow apparatus and various combinations of the activating factors was used to test the order of assembly and the role of the p47phox–p67phox complex. The data presented here are consistent with the absence of a catalytic role of the p47phox–p67phox interacting state and support the idea of independent binding sites for the cytosolic proteins on the flavocytochrome b558 allowing random binding order. However, the formation of the active complex appears to involve a synergistic process of binding of the activated cytosolic subunits to cytochrome b558. All partners should be in the vicinity for optimal assembly, a delay or the absence of one of the partners in this process seems to lead to a decrease in the efficiency of the catalytic core. The activation and assembly of the NADPH oxidase components have to be achieved simultaneously for the formation of an efficient and optimal enzyme complex. This mechanism appears to be incompatible with continuous fast exchanges of the cytosolic proteins during the production of superoxide ion in the phagosome. •No order of fixation is required for the cytosolic subunits, however all the partners should be present simultaneously.•Space control: all partners should be in the vicinity for optimal assembly.•Time control: if a subunit is missing at the beginning of the activation process an optimized edifice cannot be built.